Cardiac Embryology and Molecular Mechanisms of Congenital Heart Disease: A Primer for Anesthesiologists. (September 2016) - Kloesel, Benjamin; DiNardo, James A.; Body, Simon C.
Abstract : Congenital heart disease is diagnosed in 0.4% to 5% of live births and presents unique challenges to the pediatric anesthesiologist. Furthermore, advances in surgical management have led to improved survival of those patients, and many adult anesthesiologists now frequently take care of adolescents and adults who have previously undergone surgery to correct or palliate congenital heart lesions. Knowledge of abnormal heart development on the molecular and genetic level extends and improves the anesthesiologist's understanding of congenital heart disease. In this article, we aim to review current knowledge pertaining to genetic alterations and their cellular effects that are involved in the formation of congenital heart defects. Given that congenital heart disease can currently only occasionally be traced to a single genetic mutation, we highlight some of the difficulties that researchers face when trying to identify specific steps in the pathogenetic development of heart lesions.